Jasmonic acid pretreatment improves salt tolerance of wheat by regulating hormones biosynthesis and antioxidant capacity - Zhu, Mo; Liu, Yan; Cai, Pengkun; Duan, Xiao; Sang, Shifei; Qiu, Zongbo (Frontiers in Plant Science, 2022)
Salt stress is a severe environmental factor that detrimentally affects wheat growth and production worldwide. Previous studies illustrate that exogenous jasmonic acid (JA) significantly improved salt tolerance in plants. However, little is known about the underlying molecular mechanisms of JA induced physiochemical changes in wheat seedlings under salt stress conditions. In this study, biophysiochemical and transcriptome analysis was conducted to explore the mechanisms of exogenous JA induced salt tolerance in wheat. Exogenous JA increased salt tolerance of wheat seedlings by alleviating membrane lipid oxidation, improving root morphology, enhancing the contents of ABA, JA and SA and increasing relative water content. In the RNA-seq profiles, we identified a total of 54263 unigenes and 1407 unigenes showed differentially expressed patterns in JA pretreated wheat seedlings exposed to salt stress comparing to those with salt stress alone. Subsequently, gene ontology (GO) and KEGG pathway enrichment analysis characterized that DEGs involved in linoleic acid metabolism and plant hormone signal transduction pathways were up-regulated predominantly in JA pretreated wheat seedlings exposed to salt stress. We noticed that genes that involved in antioxidative defense system and that encoding transcription factors were mainly up- or down-regulated. Moreover, SOD, POD, CAT and APX activities were increased in JA pretreated wheat seedlings exposed to salt stress, which is in accordance with the transcript profiles of the relevant genes. Taken together, our results demonstrate that the genes and enzymes involved in physiological and biochemical processes of antioxidant system, plant hormones and transcriptional regulation contributed to JA-mediated enhancement of salt tolerance in wheat. These findings will facilitate the elucidation of the potential molecular mechanisms associated with JA-dependent amelioration of salt stress in wheat and lay theoretical foundations for future studies concerning the improvement of plant tolerance to abiotic environmental stresses.